2018
DOI: 10.2334/josnusd.17-0187
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mesenchymal stem cells on chemotaxis of osteoclast precursor cells

Abstract: Regeneration of tissue, including bone, using mesenchymal stem cells (MSCs) has been progressing rapidly. Regeneration of bone requires the presence of an appropriate environment and efficient chemotaxis of cells to the target site. Differentiation of MSCs into mesenchymal cells has received considerable attention, but the effect of MSCs on chemotaxis is not well understood. In this study, we investigated the effect of MSCs on chemotaxis of RAW264 cells via C-C motif chemokine ligand 2 (CCL2). Balb/c mouse bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…After this, a fluorescent marker of mouse macrophage cell line (RAW264.7) differentiation was injected into the mice tail vein; thereafter, the RAW264.7 cell fluorescent label was visible at the MSC transplantation site of the calvarial bone (Abe et al, ). RAW264.7 cell chemotaxis significantly increases when they are co‐cultured with MSCs in vitro (Sumi et al, ). These findings suggest that MSCs have a paracrine effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this, a fluorescent marker of mouse macrophage cell line (RAW264.7) differentiation was injected into the mice tail vein; thereafter, the RAW264.7 cell fluorescent label was visible at the MSC transplantation site of the calvarial bone (Abe et al, ). RAW264.7 cell chemotaxis significantly increases when they are co‐cultured with MSCs in vitro (Sumi et al, ). These findings suggest that MSCs have a paracrine effect.…”
Section: Discussionmentioning
confidence: 99%
“…We developed an alveolar bone regeneration method in patients with CL/P using human bone marrow mesenchymal stem cells (hBMSCs). The transplantation of hBMSC regenerated bone in a canine alveolar cleft model and orthodontic tooth movement was achieved in the regenerated bone (Sumi et al, ; Tanimoto et al, ; Yoshioka et al, ). However, puncture of the iliac bone is still necessary for bone marrow aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…OC precursors are reportedly derived from monocytes. The MCP-1 is a monocytic, chemotactic protein that promotes monocyte and lymphocyte chemotaxis and increases IL-1 and IL-6 production 4,31) . The protein may induce OC formation by accelerating the accumulation and induction of OC precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, developing an effective cure for MRONJ remains a challenge. Past reports have indicated that treatment using mesenchymal stem cell-conditioned medium (MSC-CM), a culture supernatant of bone marrow-derived stem cells, is effective 4,5) . However, collecting the bone marrow fluid from patients is an invasive process requiring clinical caution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mature osteoblasts, this MCP-1mediated interaction may start earlier in the osteoclast lineage. Using the RAW264 cell line as a model for osteoclast progenitors, Sumi et al (2018) showed that mesenchymal stem cells produce MCP-1 as a chemotactic signal for osteoclast progenitors via MCP-1's receptor, CCR2 [34]. Subsequently, MCP-1 has been recognised as a regulator of osteoclast biology as a pro-survival and pro-differentiation agent.…”
Section: The Role Of Mcp-1 In Bone Remodellingmentioning
confidence: 99%